2014
DOI: 10.1179/1743676114y.0000000146
|View full text |Cite
|
Sign up to set email alerts
|

Leaching behaviour of cementitious nuclear wasteforms containing caesium and strontium

Abstract: The leaching behaviour and physicochemical properties of cementitious nuclear wasteforms containing caesium and strontium waste simulants has been investigated. The cement wasteform consisted of a 9∶1 blend of blast furnace slag and ordinary Portland cement. Both non-loaded samples and samples that were waste loaded with 3 wt-% caesium and strontium added as nitrates have been studied. The cement hydration phases in the samples were identified, and the porosity and microstructure were analysed before leaching.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…It can be inferred that decalcification Frontiers in Nuclear Engineering frontiersin.org due to high ionic strength caused the increase in Sr retardation by NRVB in the presence of 0.1 mol dm −3 NaCl/KCl solution in the current work. These observations also seem to be in agreement with the work by Gashier et al (2014), who reported that the introduction of Sr (as Sr(NO 3 ) 2 ) into 9:1 blast furnace slag:OPC blends resulted in inhibition of Portlandite formation and an increase of the leaching rate of Ca 2+ .…”
Section: Through-diffusionsupporting
confidence: 92%
“…It can be inferred that decalcification Frontiers in Nuclear Engineering frontiersin.org due to high ionic strength caused the increase in Sr retardation by NRVB in the presence of 0.1 mol dm −3 NaCl/KCl solution in the current work. These observations also seem to be in agreement with the work by Gashier et al (2014), who reported that the introduction of Sr (as Sr(NO 3 ) 2 ) into 9:1 blast furnace slag:OPC blends resulted in inhibition of Portlandite formation and an increase of the leaching rate of Ca 2+ .…”
Section: Through-diffusionsupporting
confidence: 92%
“…wet granular ion-exchangers, slurries, etc.). There are numerous different cement systems that have been implemented or proposed to be used as waste forms, including Portland cement and its blends, 11 calcium aluminate cement and its modifications with sulfate or phosphate, 12,13 magnesium silicate or phosphate cement, 14,15 as well as various types of alkali-activated cements. [16][17][18] In choosing a suitable cement system for encapsulation of spent ion-exchangers, there are two important aspects to consider: firstly, the interactions between the ion-exchangers and the cement binder (chemical and dimensional stability); secondly, the partition (or redistribution) of radioelements between the spent ion-exchangers and the cement binder itself.…”
Section: Introductionmentioning
confidence: 99%
“…The high concentration of Ca (OH) 2 in the solutions may be due to the replacement of Ca +2 by Sr +2 , which offers more pores filled by water. The presence of these ions Sr +2 , Ca +2 , Na +1 , Si +4 , Al +3 , Cl -1 , and Fe +2 in the solution increases its alkalinity [24][25][26][27] Ca-C-S-H+ Sr +2 (aq) ↔Sr-C-S-H (s) +Ca +2 (aq) (Eq. 03) Figures (4 b-d), illustrate the effect of gamma radiation on the leachability of cement blocks, either pure cement or cement containing chlorides of elements separately or a mixture.…”
Section: A-chemical Analysismentioning
confidence: 99%